COVID-19 clinical outcomes and risk factors in fully vaccinated hemodialysis patients: A single-center prospective cohort study - Rysyev, A.; Poperechnyi, I.; Chernianu, D.; Filonov, V.; Pyankovskyi, S.; Khyzhuna, A. (Ukrainian Journal of Nephrology and Dialysis, 2022)
Hemodialysis patients (HD) are at high risk for coronavirus infection (COVID-19) and associated adverse outcomes compared with the general population. Although vaccination against SARS-CoV-2 has played an important role in stemming the spread of COVID-19 in the general population, the characterization of vaccine efficacy in dialysis patients is based primarily on humoral responses, whereas clinical data are generally not available. The aim of this study was to determine the incidence of COVID-19, clinical outcomes, and risk factors for SARS-CoV-2 infection in fully vaccinated HD patients. Methods. Of 186 HD patients treated at Link-Medital LLC Medical Center (Odesa, Ukraine) between March 2020 and March 2022, 170 patients aged 53.5 (44-63.5) years were enrolled in this prospective observational cohort study and followed up one year after completion of vaccination. Among them were 67 (39.4%) HD patients who were fully vaccinated against COVID-19 with BNT162b2 (Pfizer-BioNTech) or Moderna-mRNA-1273 mRNA vaccines and 103 (60.6%) unvaccinated HD patients. The outcomes assessed were COVID-19 morbidity and severity, hospitalization, and death associated with COVID-19. Results. During the 12-month follow-up, nearly half of 83/170 (48.8%) patients became infected with SARS-CoV-2, including 18/67 (26.7%) vaccinated patients and 65/103 (63.1%) unvaccinated patients (χ2 = 10.8; p = 0.001). The incidence rate of COVID-19 was 27 (95% CI 16, 42) in vaccinated patients at our center and 63 (95% CI 49, 80) per 100 patient-years (p = 0.001) in unvaccinated patients. Cox proportional hazards regression analysis showed that vaccinated HD patients had a statistically significant lower risk of hospitalization [HR = 0.2 (95%CI 0.1;0.4)] and need for oxygen support [HR = 0.19 (95%CI 0.09; 0.38)] compared with unvaccinated patients. Kaplan-Meyer analysis of COVID-19-associated mortality demonstrated a significantly higher survival of vaccinated HD patients compared with unvaccinated (χ2 = 4.6, log-rank p = 0.03). Further multivariate logistic analysis showed that age over 65 years, obesity, low adequacy of HD and duration of more than 5 years, anemia, low levels of parathyroid hormone (PTH) and high-density lipoprotein cholesterol (HDL-C), elevated CRP, arterial hypertension, and other cardiovascular diseases (CVD) significantly increased the risk of SARS-CoV-2 infection in fully vaccinated HD patients. Conclusions. Vaccination against COVID-19 is associated with a reduction in morbidity, hospitalization rates, and mortality in HD patients. Age over 65 years, obesity, low adequacy of HD and its duration of more than 5 years, anemia, low PTH and HDL-C levels, elevated CRP, arterial hypertension, and other CVDs significantly increased the risk of SARS-CoV-2 infection in fully vaccinated HD patients.